AI and the Future of Artistic Work: Perceptions, Impacts, and Adaptation Strategies - Petrović, Marko; Nowak, Katarzyna; Ivanova, Elena (CV TOPAZART, 2025)
Artificial intelligence (AI) tools capable of producing images, music, and literature have accelerated debates about the future of creative professions. This study examines perceptions of AI’s impact on artists’ work, focusing on the extent to which creative professionals and art students believe AI will replace, complement, or transform artistic practice. Using a survey of 250 participants (150 professional artists and 100 art students), the results reveal substantial concern regarding job displacement, balanced by optimism for new creative opportunities. The study contributes to an evidence-based understanding of AI’s implications for the art industry and outlines strategic adaptation pathways to ensure human creativity remains central in an AI-driven cultural landscape.